Anomali Sistem Pemerintahan Presidensial Pasca Amandemen UUD 1945 - M. Yasin al-Arif (Jurnal Hukum IUS QUIA IUSTUM, 2015)
Despite the fact that reformation has been running for 16 years, the idea of strengthening the Presidential System remains a discourse and even worse, it is getting weaker and causing anomalies or irregularities here and there. The first research problem is what is the cause of the anomaly in government presidential system after the amendment of Law of 1945? Second, how to establish an effective government presidential system for the benefit of government in Indonesia? This is a normative research with legal and conceptual approaches. The study discovers that the first anomaly presidential system following the amendment of the 1945 Constitution is influenced by three reasons: (i) a blend of a multiparty system with a presidential system, (ii) the occurrence of a coalition in a presidential system, and (iii) the reduction of presidential powers after the amendment. Second, it requires several steps to establish a presidential system: (i) simplification of political parties; (ii) strengthening the functions and performance of the political parties; (iii) forming a permanent coalition of political parties; (iv) revoking legislative authority of the president; (v) authorizing the presidential veto in the passage of legislation; (vi) depending on leadership style of the president; vii) implementing a district election system.